Penyuluhan Inovasi Produk SAMURAI (Spray Anti Nyamuk Dari Serai) Untuk Mengantisipasi Nyamuk - Hakim, Nafisa Ilmi; Pratiwi, Farika Nadiya; Yanti, Siti Nurma; Maulidiah, Yovina Ika; Firdausi, Vidia Cahya; Zahira, Anisya Syafa; Shodiq, Fatiha Asy Syifa; Kamila, Nadia Safa (UNEJ e-Proceeding, 2023)
Background: Mosquitoes are insects that are dangerous to humans because they can cause various diseases, including dengue hemorrhagic fever (DHF), malaria, and elephantiasis. Mosquitoes transmit this disease to humans; therefore, controlling the mosquito vector by breaking its life chain, including using mosquito repellent is necessary. Lemon grass (Cymbopogon nardus L.) is a natural ingredient containing geraniol and citronellal, which functions as an anti-mosquito. This community service activity aims to educate the people of Suci Village, Panti District, Jember Regency, regarding the formulation for using natural mosquito spray from lemon grass with the product name SAMURAI (Anti-Mosquito Spray from Serai). Method: This community service activity has several methods, namely lectures, questions, and answers, and filling in pre-test and post-test sheets to measure community knowledge regarding SAMURAI products. At the time of counselling, samples related to SAMURAI products were also given to the community. Conclusion: After conducting education, it can be seen that public knowledge has increased regarding the use of natural anti-mosquito formulations from lemongrass. The increased pre-test to post-test results evidence this. The community also welcomed this counseling well and enthusiastically.Keywords: dengue hemorrhagic fever, mosquito repellent, lemon grass.